Canon in China's office equipment market. - Foo, Yu Yuan. (2008)
A study of Canon's office equipment operations in China. An analysis is done on the competition(Hewlett Packard, Epson and the local brands) and restrictions faced by Canon. Finally, recommendations for increasing Canon's market share is provided.